Different worldviews as impediments to integrated nature and cultural heritage conservation management : experiences from protected areas in Northern Sweden - Österlin, Carl; Schlyter, Peter; Stjernquist, Ingrid (Sustainability, 2020)
In the management of protected nature areas, arguments are being raised for increasingly integrated approaches. Despite an explicit ambition from the responsible managing governmental agencies, Swedish Environmental Protection Agency and Swedish National Heritage Board, attempts to initiate and increase the degree of integrated nature and cultural heritage conservation management in the Swedish mountains are failing. The delivery of environmental policy through the Swedish National Environmental Objective called Magnificent Mountains is dependent on increased collaboration between the state and local stakeholders. This study, using a group model building approach, maps out the system's dynamic interactions between nature perceptions, values and the objectives of managing agencies and local stakeholders. It is identified that the dominance of a wilderness discourse influences both the objectives and management of the protected areas. This wilderness discourse functions as a barrier against including cultural heritage conservation aspects and local stakeholders in management, as wilderness-influenced objectives are defining protected areas as environments "untouched" by humans. A wilderness objective reduces the need for local knowledge and participation in environmental management. In reality, protected areas depend, to varying degrees, on the continuation of traditional land-use practices. © 2020 by the authors. Open access